A layered oxide positive electrode material with low volume change during charge and discharge and a preparation method thereof

By using a layered oxide positive electrode material with the chemical formula of NaxMa[MbNicMnd]O2 in sodium ion batteries, the electrostatic repulsion force is reduced through elemental replacement, and the problem of severe volume changes in Ni-Mn-based materials during charging and discharging are solved. The structural stability and cycle life of the material have been improved.

CN115939368BActive Publication Date: 2025-02-11DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211496836.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-02-11
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

In sodium ion batteries, Ni-Mn-based materials are prone to harmful P2-O2 phase transitions during charging and discharging, resulting in severe material volume changes, unstable structure and short cycle life.

Method used

Using a layered oxide positive electrode material with the chemical formula of NaxMa[MbNicMnd]O2, specific elements (such as Mg, Li, Zn, Al, K, Ti, V, Cr, Fe, by introducing specific elements into the Na layer and transition metal layers, Co, Cu) replaces elements to reduce electrostatic repulsion and avoid slippage.

Benefits of technology

Effectively suppressed P2-O2 phase transition, reduced the volume change rate of the material, improved the structural stability and cycle life of the material, maintained a 150 cycle capacity of 90.5%, and showed good performance after aging in air and water. Electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115939368B_ABST
    Figure CN115939368B_ABST
Patent Text Reader

Abstract

The present invention discloses a layered oxide positive electrode material with low volume change during charge and discharge and a preparation method thereof. The general formula of the layered oxide positive electrode material is Na x M a [M b Ni c Mn d ]O2, wherein Ni and Mn are transition metal elements, Ma and Mb are metal elements substituted by Na layer and transition metal layer respectively, and Ma is Mg 2+ , Ca 2+ and Zn 2+ One or more elements in, Mb is Li + 、Al 3+ 、K+、Ti 4+ 、V 3+ Cr 5+ , Fe 3+ 、Co 3+ and Cu 2+ One or more elements in the Na layer, 0.67≤x≤0.85, 0.03≤a≤0.1, 0.05≤b≤0.3, 0.9≤b+c+d≤1, 0.03≤c≤0.3, 0.6≤d≤0.7. In the Na layer, the electrochemically inactive metal acts as the pillar of the material, supporting the material, and the material will not slip during the charge and discharge process; in the transition metal layer, the Ni 2+ / 4+ and Mn 3+ / 4+ The Jhan-Teller effect is induced. There is no P2-O2 phase change in the positive electrode material during the charge and discharge process, which reduces the volume change rate of the material and improves the cycle life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium battery materials and relates to a layered oxide positive electrode material with low volume change during charging and discharging and a preparation method thereof. Background Art

[0002] Sodium-ion batteries (SIBs) have become a strong candidate for large-scale energy storage systems due to their low cost and similar physical and chemical properties to lithium-ion batteries. For sodium-ion batteries, the positive electrode material greatly limits their energy density and operating voltage. Research on high-performance and low-cost positive electrode materials is critical to the development of sodium-ion batteries. At present, it is generally believed that the positive electrode materials with application prospects include transition metal layered oxides, polyanion compounds, Prussian blue compounds and organic compounds. Among them, transition metal layered oxides NaxTMO2 (TM: transition metals, Ti, Mn, Fe, Co, Ni, Cu.etc) have great practical application potential due to their simple synthesis, excellent electrochemical properties and convenience of industrialization.

[0003] P2-type layered oxides have high reversible specific capacity and stable crystal structure, making them a promising cathode material for sodium-ion batteries. 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 has attracted widespread attention due to its high capacity and working voltage. However, when charged to about 4.2V, the sodium ion content in the system is low, and the electrostatic repulsion between two adjacent transition metal layers increases, driving the transition metal layers to slip relative to each other to reduce the capacity of the system to achieve a stable structure. In this process, the so-called P2-O2 phase transition occurs. This will bring about a drastic volume change, resulting in material structure destruction and poor stability.

[0004] How to solve the harmful P2-O2 phase transition of Ni-Mn-based materials during the charging and discharging process, reduce the volume change of the material, and improve the structural stability and cycle life of the material is a difficult problem that needs to be solved urgently in this field. Summary of the invention

[0005] In view of this, the present invention provides a layered oxide positive electrode material with low volume change during the charge and discharge process and a preparation method thereof, which solves the problem of structural damage of the layered oxide due to excessive Na ion deintercalation at high voltage, and the cycle life of the material is greatly improved, which has great practical value.

[0006] In the first aspect, the present invention discloses a layered oxide positive electrode material with low volume change during charge and discharge, the chemical formula of which is Na x M a [M b Nic Mn d ]O2;

[0007] Among them, Ni and Mn are transition metal elements. a and M b are the metal elements replaced by the Na layer and the transition metal layer, M a Mg 2+ , Ca 2+ and Zn 2+ One or more elements in M b For Li + 、Al 3+ , K + 、Ti 4+ 、V 3+ Cr 5+ , Fe 3+ 、Co 3+ and Cu 2+ One or more elements, x, a, b, c and d are the molar ratios of the corresponding elements, 0.67≤x≤0.85, 0.03≤a≤0.1, 0.05≤b≤0.3, 0.9≤b+c+d≤1, 0.03≤c≤0.3, 0.6≤d≤0.7; each component satisfies charge conservation and stoichiometric conservation.

[0008] The molar ratio of Mb / Ma is 1.5-3.

[0009] In another aspect, the present invention provides a method for preparing the layered oxide positive electrode material, comprising: b The oxide, carbonate, hydroxide or nitrate of the present invention is mixed with a sodium source and calcined to obtain a primary product; the primary product is mixed with M a The oxide, carbonate, hydroxide, nitrate or acetate of M is mixed and calcined twice to obtain a layered oxide positive electrode material; or M a Oxides, carbonates, hydroxides or nitrates of b The oxide, carbonate, hydroxide, nitrate or acetate of the present invention is mixed with a sodium source and calcined to obtain a layered oxide positive electrode material.

[0010] The sodium source is sodium carbonate, sodium nitrate or sodium acetate.

[0011] The calcination temperature is 850-1000°C, the calcination time is 8h-24h, and the calcination atmosphere is air, oxygen or nitrogen.

[0012] In a third aspect, the present invention provides a positive electrode sheet for a sodium ion secondary battery, comprising the layered oxide positive electrode material. More specifically, the positive electrode sheet comprises a current collector, a conductive additive coated on the current collector, a binder, and the layered oxide positive electrode material.

[0013] In a fourth aspect, the present invention also provides a sodium ion secondary battery, comprising the positive electrode sheet.

[0014] The beneficial effects of the present invention are as follows:

[0015] The elements Ni, Mn, etc. contained in the P2-type layered oxide positive electrode material provided by the present invention are all non-toxic and safe elements; through element substitution, in the Na layer, the electrochemically inactive metal serves as the pillar of the material, supporting the material, and the material will not slip during the charge and discharge process; in the transition metal layer, the Ni 2+ / 4+ and Mn 3+ / 4+ Based on the Jhan-Teller effect, the layered oxide cathode material used in sodium ion secondary batteries does not undergo P2-O2 phase transition during the charge and discharge process, and reduces the volume change rate of the material to only 0.65%, so it has excellent cycle performance. -1 The capacity retention rate of 150 cycles at the current density is 90.5%, and it also has a good specific capacity (130mAh g -1 ). Unlike most water-sensitive P2-type oxide cathode materials, the material also shows excellent structural stability after being treated with water and air. The material structure does not change after aging in air and water, and the electrochemical performance is almost unchanged. In addition, the layered oxide cathode material is prepared by a simple high-temperature solid-phase reaction, which is simple to operate, low-cost, and easy to industrialize. Therefore, the sodium-ion full battery constructed with layered oxide cathode materials has high energy density and long cycle life, and has great application value. It can be used in large-scale energy storage equipment such as solar energy, tidal energy, wind power generation, smart grids, and distributed power stations. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0017] Figure 1 The XRD test results of different embodiments of the present invention are shown in FIG.

[0018] Figure 2 The charge and discharge curves of the first three cycles of Example 1 of the present invention at a rate of 0.1C;

[0019] Figure 3 The performance diagram of 150 cycles at 1C rate of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention;

[0020] Figure 4This is an in-situ XRD test result diagram of Example 1 of the present invention during the first week of charge and discharge process at a rate of 0.2C;

[0021] Figure 5 This is a graph of XRD test results of Example 1 of the present invention after aging in air and water;

[0022] Figure 6 This is a long cycle performance diagram of Example 1 of the present invention after aging in air and water;

[0023] Figure 7 The charge and discharge curves of the first three cycles of Example 2 of the present invention at a rate of 0.1C;

[0024] Figure 8 The charge and discharge curves of the first three cycles of comparative example 1 of the present invention at a rate of 0.1C;

[0025] Fig. 9 The charge and discharge curves of the first three cycles of comparative example 2 of the present invention at a rate of 0.1C;

[0026] Fig.10 The charge and discharge curves of the first three cycles of comparative example 3 of the present invention at a rate of 0.1C;

[0027] Fig.11 This is the charge and discharge curve of the first week of comparative example 4 of the present invention at a rate of 0.1C;

[0028] Fig.12 This is the charge and discharge curve of the first week of comparative example 5 of the present invention at a rate of 0.1C; DETAILED DESCRIPTION

[0029] The present invention will be further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereby.

[0030] Example 1

[0031] Anhydrous sodium carbonate, lithium hydroxide monohydrate, nickel oxide, and manganese dioxide were mixed in a molar ratio of Na, Li, Ni, and Mn of 0.75:0.15:0.1:0.7, and ground in an agate mortar for 10 minutes. For further mixing, the materials were placed in a planetary ball mill and continued to be ball-milled for 5 hours at a speed of 400 r / min to obtain a precursor; the obtained precursor was pressed and mixed and then transferred to a corundum boat, and treated in a muffle furnace at 900°C for 15 hours to obtain a black powder layered oxide material (primary product) Na 0.75 [Li 0.15 Ni 0.1 Mn 0.7]O2, the layered oxide material powder and magnesium oxide were mixed again according to the molar ratio of Na to Mg of 0.75:0.05, the mixture was pressed into tablets and treated in a muffle furnace at 900°C for 15h to obtain a black powder layered oxide positive electrode material Na 0.75 Mg 0.05 [Li 0.15 Ni 0.1 Mn 0.7 ]O2, XRD diffraction patterns are as follows Figure 1 As shown in the figure, the XRD results show that the material is a P2 phase layered oxide, and the superlattice peak near 22.5° indicates that there is an ordered arrangement of TM1 / TM2 in the material. It is well known that the Mg site in the TM layer can inhibit the ordered arrangement of the transition metal layer, indicating that the Mg in the material did not enter the TM layer but entered the Na layer.

[0032] The layered oxide prepared as above is used as the positive electrode active material for the preparation of sodium ion batteries. The specific steps are: the prepared layered oxide positive electrode material is mixed with Super-P and polyvinylidene fluoride (PVdF) in a mass ratio of 8:1.5:0.5 in N-methyl-2-pyrrolidone (NMP). Then the mixed slurry is evenly coated on aluminum foil and vacuum dried at 100°C for 10 hours to obtain a positive electrode sheet. The loading amount of the positive electrode sheet is 3-4 mg / cm 2 . CR2032 button cells were assembled in an argon glove box with water and oxygen content less than 0.1ppm. The layered oxide material was used as the positive electrode, the sodium sheet was used as the negative electrode, the glass fiber membrane GF / F was used as the separator in the middle, and the electrolyte was NaPF6 / (PC:FEC=95:5). In a 30℃ constant temperature box, constant current charge and discharge tests were performed on the Blue Electric Battery Test System with a voltage range of 2-4.35V. The test results are as follows Figure 2 and Figure 3 As shown, its reversible specific capacity can reach 130 mAh / g, and it has good cycle performance. The capacity retention rate of the material is 90.5% after 150 cycles at a current density of 0.1 mAg-1.

[0033] The layered oxide prepared as above was used as the positive electrode active material for in-situ XRD testing to calculate its volume change rate during the charge and discharge process. The specific steps are: slurry preparation according to the above steps, coating the mixed slurry on the metal beryllium sheet, and vacuum drying at 100°C for 10 hours. The in-situ cell was assembled in an argon glove box with a water and oxygen content of less than 0.1ppm. The in-situ test was carried out at a current density of 20mA / g using a constant current charge and discharge mode. The test results are shown in Figure 2. Figure 4 As shown, it can be seen that no phase change occurs during the charge and discharge process, and the calculated volume change rate is only 0.65%.

[0034] The above layered oxide material was subjected to air and water aging treatments. The air aging conditions were: 10 days and 30 days in the air; the water aging conditions were: stirring in deionized water for 1 hour. The results are as follows: Figure 5 and Figure 6 As shown, XRD still shows the P2 phase structure and the material structure has not changed; the electrochemical test process is the same as that of the unaged layered oxide, and the results show that the electrochemical performance has hardly decayed.

[0035] Example 2

[0036] The specific preparation process and experimental conditions are the same as those in Example 1, but the magnesium oxide in the precursor oxide is replaced by zinc oxide, and the layered oxide positive electrode material of the black powder is Na 0.75 Zn 0.05 [Li 0.15 Ni 0.1 Mn 0.7 ]O2. Its XRD spectrum is as follows Figure 1 ,From the XRD results, the material is a P2-type layered oxide, Zn enters the sodium layer, and Li enters the transition metal layer.

[0037] The layered oxide prepared as above was used as the positive electrode active material for the preparation and testing of sodium ion batteries. The preparation process of the positive electrode sheet and the electrochemical testing method were the same as those in Example 1. The test results are shown in Figure 7 After replacing Mg with Zn, it also has excellent electrochemical performance, with a reversible capacity of 140 mAh g -1 ; Long loop results are as follows Figure 3 , at 0.1mAg -1 The capacity retention rate after 150 cycles at the current density is 91.5%.

[0038] Example 3

[0039] The specific preparation process and experimental conditions are the same as those in Example 1, but the stoichiometric ratios of anhydrous sodium carbonate, magnesium oxide, lithium hydroxide monohydrate, nickel oxide, and manganese dioxide in the precursor compound are different, and the layered oxide positive electrode material of the obtained black powder is Na 0.75 Mg 0.1 [Li 0.15 Ni 0.05 Mn 0.7 ]O2. Its XRD spectrum is as follows Figure 1 ,From the XRD results, the material is a P2-type layered oxide, Mg enters the sodium layer, and Li enters the transition metal layer.

[0040] Comparative Example 1 (not according to the present invention)

[0041] The specific preparation process and experimental conditions are the same as those in Example 1, but the stoichiometric ratios of anhydrous sodium carbonate, lithium hydroxide monohydrate, nickel oxide, and manganese dioxide in the precursor compound are different, and the layered oxide material of the black powder obtained is Na 0.75 Li 0.15 Ni 0.15 Mn 0.7 O2. Its XRD spectrum is as follows Figure 1 ,From the XRD results, the material is a P2 type layered oxide.

[0042] The layered oxide prepared as above was used as the positive electrode active material for the preparation and testing of sodium ion batteries. The preparation process of the electrode sheet and the electrochemical testing method were the same as those in Example 1. The test results are shown in Figure 3 and Figure 8 , compared with Example 1, the cycle and rate performance are reduced and the material structure is unstable.

[0043] Comparative Example 2 (not according to the present invention)

[0044] The specific preparation process and experimental conditions are the same as those in Example 1, but the stoichiometric ratios of anhydrous sodium carbonate, magnesium oxide, nickel oxide, and manganese dioxide in the precursor compound are different, and the layered oxide material of the black powder is Na 0.75 Mg 0.05 [Ni 0.25 Mn 0.7 ]O2. Its XRD spectrum is as follows Figure 1 ,From the XRD results, the material is a P2 type layered oxide.

[0045] The layered oxide prepared as above was used as the positive electrode active material for the preparation and testing of sodium ion batteries. The preparation process of the positive electrode sheet and the electrochemical testing method were the same as those in Example 1. The test results are shown in Figure 3 and Fig. 9 , compared with Example 1, the cycle and rate performance are reduced and the material structure is unstable.

[0046] Comparative Example 3 (not according to the present invention)

[0047] The specific preparation process and experimental conditions are the same as those in Example 1, but the stoichiometric ratio of anhydrous sodium carbonate, nickel oxide, and manganese dioxide in the precursor compound is different, and the layered oxide material of the black powder is Na 0.75 Ni 0.3 Mn 0.7 O2. Its XRD spectrum is as follows Figure 1 ,From the XRD results, the material is a P2 type layered oxide.

[0048] The layered oxide prepared as above was used as the positive electrode active material for the preparation and testing of sodium ion batteries. The preparation process of the positive electrode sheet and the electrochemical testing method were the same as those in Example 1. The test results are shown in Figure 3 and Fig.10 ,It can be seen that the samples without Mg and Li doping have a large voltage platform above 4.2 V, which corresponds to the P2-O2 phase transition process. The capacity retention rate after 150 cycles at 1C rate is only 64.3%.

[0049] Comparative Example 4 (not according to the present invention)

[0050] The specific preparation process and experimental conditions are the same as those in Example 1, but the stoichiometric ratios of anhydrous sodium carbonate, magnesium oxide, lithium hydroxide monohydrate, nickel oxide, and manganese dioxide in the precursor compound are different, and the layered oxide material of the black powder obtained is Na 0.75 Li 0.03 Mg 0.15 Ni 0.18 Mn 0.64 O2. The charging and discharging results are as follows Fig.11 As shown in the figure, compared with Example 1, the electrochemical performance decreases with the increase of Mg content.

[0051] Comparative Example 5 (not according to the present invention)

[0052] The specific preparation process and experimental conditions are the same as those in Example 1, but the stoichiometric ratios of anhydrous sodium carbonate, magnesium oxide, nickel oxide, and manganese dioxide in the precursor compound are different, and the layered oxide material of the black powder is Na 0.8 Mg 0.15 Ni 0.25 Mn 0.6 O2. The charging and discharging results are as follows Fig.12 As shown in the figure, the charging curve in the first week has many voltage steps and platforms, and the stability is poor.

Claims

1. A layered oxide positive electrode material with low volume change during charge and discharge, characterized in that: The chemical formula is Na x M a [M b Ni c Mn d ]O2; Among them, Ni and Mn are transition metal elements. a and M b are the metal elements replaced by the Na layer and the transition metal layer, M a Mg 2+ and Zn 2+ One or more elements in M b For Li + , x, a, b, c and d are the molar ratios of the corresponding elements, 0.67≤x≤0.85, 0.03≤a≤0.1, 0.05≤b≤0.3, 0.9≤b+c+d≤1, 0.03≤c≤0.3, 0.6≤d≤0.7; each component satisfies the conservation of charge and the conservation of stoichiometry; the molar ratio of Mb / Ma is 1.5-3; The method for preparing the layered oxide positive electrode material comprises the following steps: b The oxide, carbonate, hydroxide or nitrate of the present invention is mixed with a sodium source and calcined to obtain a primary product; the primary product is mixed with M a The oxide, carbonate, hydroxide, nitrate or acetate of M is mixed and calcined twice to obtain a layered oxide positive electrode material; or M a Oxides, carbonates, hydroxides or nitrates of b The oxide, carbonate, hydroxide, nitrate or acetate of the present invention is mixed with a sodium source and calcined to obtain a layered oxide positive electrode material.

2. The layered oxide positive electrode material according to claim 1, characterized in that: The calcination temperature is 850-1000°C, and the calcination time is 8h-24h.

3. A positive electrode sheet for a sodium ion secondary battery, characterized in that: Comprising the layered oxide positive electrode material according to claim 1.

4. A sodium ion secondary battery, characterized in that: Including the positive electrode sheet as described in claim 3.

Citation Information

Patent Citations

  • Layered oxide positive electrode, preparation method and application thereof and sodium-ion battery containing layered oxide positive electrode

    CN111564605A

  • P2 type layered sodium ion battery positive electrode material and preparation method thereof

    CN113921809A